1986
DOI: 10.1007/bf00199362
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the cellular immune response to and adoptive immunotherapy of a BALB/c lymphoma that cross-reacts with normal DBA/2 cells

Abstract: We have previously shown that YC8, a Moloney virus-induced BALB/c lymphoma, is susceptible to lysis by BALB/c anti-DBA/2 effector cells. To further evaluate the relationship between non-H-2 antigens of DBA/2 background and tumor-associated determinants, we investigated the pattern of cytotoxic and proliferative responses induced in BALB/c mice by immunization with YC8 lymphoma. Spleen cells from tumor-immunized animals were restimulated in vitro with YC8 cells and tested for cytotoxicity on target cells of dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Followup studies employed almost the identical experimental protocol, but with the tumor implantation done before conditioning. As YC8-specific resistance seemed to be attributed to immunization of the BALB/c mice with DBA/2 splenocytes (361,412), administration of these cells (alloantigen) was paired as US together with the presentation of camphor odor as CS. The results displayed a conditioned resistance to YC8 lymphoma in female mice (177).…”
Section: Tumorsmentioning
confidence: 99%
“…Followup studies employed almost the identical experimental protocol, but with the tumor implantation done before conditioning. As YC8-specific resistance seemed to be attributed to immunization of the BALB/c mice with DBA/2 splenocytes (361,412), administration of these cells (alloantigen) was paired as US together with the presentation of camphor odor as CS. The results displayed a conditioned resistance to YC8 lymphoma in female mice (177).…”
Section: Tumorsmentioning
confidence: 99%
“…The i.v, administration of specific tumor-immune T lymphocytes can cure most mice bearing 3-day established YC8 tumors (Colombo et al, 1984;Sensi et al, 1986). Here we show that the curative activity of immune effector cells is pro~re~sively lost when the~nset of !reatment is delayed, indicating that tumor burden IS most likely a crucial factor which limits the efficacy of this therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The susceptibility of this tumor to other chemotherapeutic agents, as well as to immune effectors, has been extensively investigated in previous works (Colombo et d . , 1984;Formelli et al, 1988;Sensi et al, 1986). It was found that other anti-tumor drugs such as doxorubicin (DX) or cisplatinum (DDP) were not curative (Formelli et al, 1988).…”
Section: Bcnu Balb/c Anti-yca Donorsmentioning
confidence: 99%
“…It was found that other anti-tumor drugs such as doxorubicin (DX) or cisplatinum (DDP) were not curative (Formelli et al, 1988). Immune lymphocytes could be highly effective, but only when administered to mice bearing a small tumor (3-day tumor burden) (Colombo et al, 1984;Sensi et al, 1986). The effect of DDP, but not of DX, however, could be greatly improved by the addition of immune effectors resulting in the cure of mice bearing a 5-day tumor burden (Formelli et al, 1988).…”
Section: Bcnu Balb/c Anti-yca Donorsmentioning
confidence: 99%